Autonomous policy making by international organizations - Reinalda, Bob; Verbeek, Bertjan, 1960- (Routledge/ECPR studies in European political science, 1998)
The volume seeks to determine the ways in which IO's contribute to the solution of global problems by influencing international decision-making in ways that go beyond the lowest common denominator of national interests.